There is no crime for those who have Christ: religious violence in the Christian Roman Empire - Gaddis, Michael (The transformation of the classical heritage, 2005)
"There is no crime for those who have Christ," claimed a fifth-century zealot, neatly expressing the belief of religious extremists that righteous zeal for God trumps worldly law. This book provides an in-depth and penetrating look at religious violence and the attitudes that drove it in the Christian Roman Empire of the fourth and fifth centuries, a unique period shaped by the marriage of Christian ideology and Roman imperial power. Drawing together materials spanning a wide chronological and geographical range, Gaddis asks what religious conflict meant to those involved, both perpetrators an